2011
DOI: 10.1080/87565641.2010.549882
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity, Reproducibility, and Reliability of Self-Paced Versus Fixed Stimulus Presentation in an fMRI Study on Exact, Non-Symbolic Arithmetic in Typically Developing Children Aged Between 6 and 12 Years

Abstract: Fixed stimulus presentation times pose several methodological problems for developmental functional magnetic resonance imaging (fMRI) studies that can be avoided by self-paced study designs. Yet, methodological issues of self-paced stimulus presentation for fMRI studies are largely understudied. Therefore, we compared sensitivity, reproducibility, and reliability of neural activation of a fixed and a self-paced design for an exact, non-symbolic addition paradigm in a sample of children aged 6-12 years. Both de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In the scanner, an MR-compatible response box with four response buttons was centrally placed on the participants, and responses were given by pressing the leftmost or the rightmost button, respectively. In a recently published pilot study, we showed that this self-paced stimulus presentation paradigm was much more reliable and was at least as sensitive as a fixed stimulus presentation paradigm (Krinzinger et al, 2011). In the magnitude comparison tasks, children had to press the button corresponding to the side with the larger stimulus, and a vertical white line was always present in the middle of the black screen and also in the rest condition.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…In the scanner, an MR-compatible response box with four response buttons was centrally placed on the participants, and responses were given by pressing the leftmost or the rightmost button, respectively. In a recently published pilot study, we showed that this self-paced stimulus presentation paradigm was much more reliable and was at least as sensitive as a fixed stimulus presentation paradigm (Krinzinger et al, 2011). In the magnitude comparison tasks, children had to press the button corresponding to the side with the larger stimulus, and a vertical white line was always present in the middle of the black screen and also in the rest condition.…”
Section: Methodsmentioning
confidence: 81%
“…In addition, a child template in Talairach space was produced based on children’s brain scans obtained in another study (Krinzinger et al, 2011). Finally, this template was used for the projection of all significant brain activation maps.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the expected differences in reaction time between DD and TD, stimuli were presented in a self-paced stimulus design, which improves test-retest reliability for fMRI data [21]. Self-paced designs with a fixed number of stimuli inherently lead to an unequal number of time points between individuals.…”
Section: Methodsmentioning
confidence: 99%
“…One can increase the number of volumes by means of parallel imaging techniques, by means of task length or by means of number of sessions. Recently, we showed that the reliability of child fMRI imaging could be improved using so-called “self-paced” task designs [21]. Whereas standard fixed-pace task designs use fixed stimulus length and inter-stimulus interval (ISI), self-paced task designs follow the performance speed of the individual child and thereby avoid both possible frustration and/or boredom by adjusting difficulty to ability levels as well as by preventing mind-wandering by assuring 100% time-on-task.…”
Section: Introductionmentioning
confidence: 99%
“…A potential disadvantage is that possible observed reading time differences could be driven by effort-related processing differences. In a recent study, Krinzinger et al (2011) directly compared fMRI results of fixed and self-paced designs. The results showed that for examining the neural networks underlying complex cognitive processes, the sensitivity of a self-paced study design is at least comparable to that of a fixed design (Krinzinger et al, 2011).…”
Section: Coherence-break Detection Taskmentioning
confidence: 99%